Evaluation of the CD14-159 C/T polymorphism and endotoxin exposure in cotton textile workers: gene-environment interaction - Karakis, Pasaoglu G.; Birben, E.; Bozdogan, G.; Sackesen, C.; Kalayci, O. (WILEY-BLACKWELL, 2011)
30th Congress of the European-Academy-of-Allergy-and-Clinical-Immunology (EAACI), Istanbul, TURKEY, JUN 11-15, 2011